Speech enhancement using artificial neural network - Narmatha Parasuraman Amudha (2014)
This dissertation will investigate various methods of noise reduction in speech signals using back propagation neural networks. Neural network approach on time domain and transform domain methods are focused. A comprehensive evaluation and comparison on the performance of both time and transform domain approach is carried out. In precise network architecture, training issues and efficiency in noise reduction are investigated. In addition, speech enhancement techniques like magnitude spectral subtraction are explored and their results are discussed.